Gestão arquivística sustentável: uma proposta de manual - Albuquerque, Paulina Aparecida Marques Vieira (2015)
Demands for a consideration of environmental issues nowadays have become so prevalent and archival science could not stay out of the debate. Thus, the work presented here, in the form of a 'product', seeks to highlight the importance of implementing a sustainable document management programs that may contribute to an ecologically balanced environment. For this, we designed a sustainable archival management manual establishing a set of practices to promote environmental sustainability in the context of the Pró-Reitoria de Extensão e Cultura (Proexc) of the Universidade Federal do Estado do Rio de Janeiro (Unirio). Later, this pilot study will be extended to the entire University.